A Typological Analysis Method for Rural Dwellings: Architectural Features, Historical Transformations, and Landscape Integration: The Case of “Capo Due Rami”, Italy - Stefano Bigiotti; Mariangela Ludovica Santarsiero; Anna Irene Del Monaco; Alvaro Marucci (Land)
Focusing on the agricultural area of “Capo Due Rami” in Rome, this research aims to interpret the architectural features of the rural dwellings through a typological analysis. Drawing on data collected from direct surveys, historical records, cartographic materials, and documentary sources, the morphological and settlement evaluation of agricultural constructions refines traditional methods and techniques used in the analysis of residential models. Using specifically designed observation sheets, the study highlights how the reclamation and drainage works carried out predominantly between the 19th and 20th centuries in the area have influenced the typology of buildings and their relationship with the agricultural environment. The findings underscore that the morphotype of the dwellings in “Capo Due Rami” derives from the practical demands of agriculture and the functional requirements of rural life, incorporating targeted architectural solutions to address sanitary and environmental concerns. The observation sheets were designed to integrate qualitative indicators, drawing on previous investigative experiences in typological analysis. While adhering to established methodologies, they have been modified to reflect the cartographic and documentary data specific to “Capo Due Rami”. This approach has made it possible to highlight the distinctive features of the area, such as the proximity between buildings and reclamation canals.